Academic Writing Challenges and Strategies among Indonesian EFL Learners: A Study from Central Kalimantan - Emeral; Tutik Haryani; Dedy Arianto Bannus (JADEs Journal of Academia in English Education, 2026)
This study investigates the challenges, attitudes, and strategies of Indonesian EFL learners in academic writing, focusing on EFL learners from Central Kalimantan, a context that has received limited scholarly attention. Employing a mixed-method design, data were collected from 163 undergraduate students through questionnaires and interviews. The findings revealed that learners experienced difficulties in academic writing, with sentence structure (76%), topic familiarization (75%), and grammar (62%), emerging as the most challenging aspects. The degree of difficulty significantly varied across gender and academic year, with female and sophomore students reporting greater challenges. Despite these challenges, participants demonstrated generally positive attitudes toward academic writing, considering it essential for their academic and professional development. The participants reported various strategies to overcome difficulties, such as initiating self- and peer-review, and implementing extensive use of artificial intelligence (AI) tools like Grammarly, QuillBot, and ChatGPT. While these digital tools were perceived as beneficial in enhancing accuracy and organization, the participants also expressed caution regarding overreliance. The results emphasize the importance of developing context-specific strategies to strengthen writing practice and grammar instruction. The study contributes a contextualized understanding of EFL learners’ academic writing experiences and emphasizes the balance between human effort and technological support.